2012
DOI: 10.1016/j.gaceta.2012.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Prácticas de cribado de cáncer y estilos de vida asociados en la población de controles del estudio español multi-caso control (MCC-Spain)

Abstract: The prevalence of screening practices was high for breast, cervical and prostate cancer and was low for colorectal cancer. No common lifestyle patterns were associated with participation, although differences were found by sex and type of screening test. These results may be useful to guide further studies on screening practices and review possible inefficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
2
1
3
Order By: Relevance
“…Más del 90% de mujeres de entre 50 a 69 años se ha hecho una mamografía en los últimos 2 años, demostrando que el programa de detección precoz contra el cáncer de mama está funcionando, a la vez que las mujeres también están más sensibilizadas. Esta tendencia también se puede ver en otros estudios7, 13, 14.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Más del 90% de mujeres de entre 50 a 69 años se ha hecho una mamografía en los últimos 2 años, demostrando que el programa de detección precoz contra el cáncer de mama está funcionando, a la vez que las mujeres también están más sensibilizadas. Esta tendencia también se puede ver en otros estudios7, 13, 14.…”
Section: Discussionunclassified
“…Coincidiendo con otros estudios, las mujeres que tienen más edad, mayor nivel social, estudios superiores y que conviven en pareja se realizan más mamografías7, 17, 19, 20, 21, 22, aunque las mujeres con nivel social alto a veces se la realizan en centros privados y no participan en el programa de detección de cáncer del sistema nacional 23 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Healthy individuals made up 22.1% of the sample. In Spain, two surveys, nationally representative, carried out in an adult population and with data self-reported by the participants showed that 40% [ 24 ] and 16% [ 25 ] of the population did not have any of the chronic diseases on a preselected list of prevalent chronic diseases. The rate for individuals in the groups with the highest level of comorbidities (i.e., three or more dominant chronic diseases, malignancies or catastrophic conditions) was 2.9%, a figure similar to the 2.3% of bowel screening non-participants who had a medical reason for not participating in the Scottish programme [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review included seven studies specifically assessing the effect of having a chronic monitorable disease on colorectal cancer screening adherence, of which five reported the chronic disease as a significant facilitator [ 27 ]. In fact, two nationwide surveys performed in Spain based on self-reported data found significant higher compliance with colorectal cancer screening as the number of chronic conditions increased [ 24 ] or in the event of an existing comorbidity [ 25 ].…”
Section: Discussionmentioning
confidence: 99%